Rancangan Fasilitas Pembangkit Listrik Tenaga Sampah: Studi Kasus di Kota Medan Sumatera Utara - Simanjuntak, J P; Napitupulu, Richard A M; Lumbangaol, Partahi (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2022)
In planning a power generation system using waste as an energy source, it is necessary to conduct an initial analysis of the potential local waste available. Not all waste can be used as the source of thermal energy by burning in an incinerator. Therefore, the selection is required to obtain the suitable waste and characterization to determine the potential thermal energy content in the waste. This article aims to obtain the electrical capacity produced from local waste to generate electricity in some regions of the city of Medan. The analysis is carried out on the availability of the waste and its potential for thermal energy generated. The selected incinerator of the fixed bed type with a two-stage air supply was explained comprehensively. Minimum pollution, high thermal conversion, and ease of operation are the critical point considered for the selected incinerator. The results revealed that 50 kWe was generated from a power plant system using waste. This amount of electricity can provide electricity for 25 households in the area where the case is located. This study is expected to provide sustainable waste management to the city of Medan in converting the waste into the household electricity supply.